EKSPRESI Interleukin-1 (IL-1) PADA PERIAPIKAL AKIBAT INDUKSI BAKTERI Enterococcus faecalis - Yuliana Dwiwahyu Suryandari; Ketut Suardita; M. Mudjiono; Tamara Yuanita (Conservative Dentistry Journal, 2017)
Background. Root canal treatment is a main role in decreasing infection from root canal and pulp. The main cause of periapical damage mostly are bacteries. E.faecalis is a bactery that is found as an etiology of endodontic treatment failure. Cell wall of this bacteria is containing Lipoteichoic acid (LTA). LTA can penetrate into the periradicular tissue, act as endotoxin in host and cause periradicular inflammation and destruction. It occurs due to the capability of IL-1. IL-1 is the proinflammation cytokine that is the key of host response bacteria invation and tissue damage. Also IL-1 could cause some indirectly tissue damage through the activation of MMPS. MMPs to stop the collagen formation. Purpose. The aim of this study is to know about the expression of IL- 1 during the periapical tissue damage due to induction of E.faecalis. Method. This study used laboratory experimental with the post test only control group design. A total of 54 male rats were randomly divided into 2 main groups, which each main group had 3 subgroups. Group A (control) : every tooth was induced only by sterile BHIb. Group A had 3 subgroups (A Control day 3, 10, and 21), group B : every tooth was induced by 10 μl BHI-b E.faecalis ATCC212(106 CFU), it was contained 3 sub groups (B day 3,10, and 21). The animals were sacrificed based on their days scheduled group and prepared for histological examination of tissue damage, then we did the immunohistochemistry followed by calculation on the light microscope. Result. The analysis revealed that the expression of IL-1 increased significantly in group B when E.faecalis was induced. Conclusion. From this study we know that the expression of IL-1 is increasing during the periapical tissue damage that induced by E.faecalis.